Foot Health Education for People with Rheumatoid Arthritis: '…. A Game of Chance…' – A Survey of Patients' Experiences. (15th June 2015) - Graham, Andrea S.; Williams, Anita E.
Abstract: Objective: Up to 90% of people with rheumatoid arthritis (RA) experience foot problems leading to reduced function, mobility, quality of life and social participation, and impacts on body image, but these can be improved with general foot care, orthoses, footwear and patient education. Foot health patient education is lacking, so the aim of the present study was to identify the foot health educational needs of people with RA in relation to its content, timing, mode of delivery and the perceived barriers to its provision. Methods: People with RA completed an online survey and provided free‐text comments for thematic analysis. Results: A total of 249 people completed the free‐text section of the survey. Five main themes emerged: 'Forgotten feet'; 'Too little, too late'; 'Lacks and gaps'; 'I am my feet' and 'Game of chance'. Conclusion: Foot pathology in people with RA has a bio‐psychosocial impact on their lives. Foot health and related information appears to be considered rarely within the medical consultation. Access to foot health information and services is limited owing to a lack of patient and/or health professional awareness, with a detrimental impact on the prognosis of their foot health. The importance of foot health in people with RA should be reinforced for patients and health professionals alike. Opportunities to discuss foot health within the medical consultation should be provided regularly. Copyright © 2015 John Wiley & Sons, Ltd.